A Critical Analysisof The Existing: Maqasid-Based Welfare Indices - Suliswanto, Muhammad Sri Wahyudi; Mahyudi, Mohd.; Nizam Barom, Mohd. (Journal of Contemporary Maqasid Studies, 2024)
Maqasid al-Shariah based welfare measurement is a welfare measurement tool that covers all dimensions of welfare, both material and non-material. According to the Maqasid al-Shariah theory put forward by Al-Ghazali and Al-Shatibi; which was later expanded further into the socio-economic context (Chapra, 2008). Chapra is talking about how we need to expand the application of al-Maqasid to make it more practical and effective. This is because al-Maqasid is a philosophical principle that needs to be simplified so that it can be put into practice. Many contemporary researchers have implemented maqasid al-shariah in measuring development or welfare instruments with various modifications related to the sub-variables. However, most of them give equal weight to each maqasid component. Even though most Muslim scholars give different priorities to each maqasid component. Therefore, this study will criticize 15 articles on the maqasid-based welfare index as a first step to propose improvements to the maqasid-based welfare index measurement. To achieve the research objectives, the method used in this research is an integrative literature review. This study proposes an index and indicator model in integrating the five dimensions of Maqasid al-Syariah in measuring welfare.